Application De La Télédétection Et Du Sig Au Suivi Des Formations Végétales De La Forêt Classée Des Trois Rivières Au Nord-Est Du Bénin - Zakari, Soufouyane; Imorou, Ismaïla Toko; Thomas, Omer A. B.; Djaouga, Mama; Arouna, Ousséni (European Scientific Journal, ESJ, 2018)
The creation of protected areas was intended to counter the advance of the agricultural front and other forms of pressure on natural ecosystems, but today these pressures strongly affect these protected areas. The dynamics of the vegetation was studied in Trois RiviÃ¨res forest reserve in north-eastern Benin, based on Remote Sensing and GIS techniques. This study aims to analyse the vegetation evolution and determine the drivers of that dynamics using 1995 Landsat TM, 2013 Landsat OLI-TIRS imageries and field surveys. The supervised classification based on the â€˜â€˜Maximum likelihoodâ€™â€™ algorithm was derived from ENVI 5.0 software. The transition matrix derived from Intersect function of ArcToolbox in ArcGIS 9.3 software was used to calculate the different conversion of land cover. The transition matrix was used to measure the intensities and speeds of land cover categories changes from ’PontiusMatrix22’ ’and’ ’Intensity Analysis02 programs. In addition, 200 household were surveyed from individual interviews and focus group on questionnaires and interview guides basis. The results show that the forest formations decreased from 48 % in 1995 to 20.4 % in 2013. The mosaics of fields and fallows have increased from 3 % to 24 %. The intensity change per land cover category shows that tree and shrub savannahs occurred the most significant change of 73 % of the study area with a 34 % of gain, 32 % of stability and 7 % of loss. In the order hand, the mosaics of fields and fallows, built up areas and dry dense forests occurred the biggest change. According to the perceptions of surveyed people, agriculture, logging and charcoal production are the main direct drivers of Trois RiviÃ¨res forest reserve degradation.